The DeltaN p63 Promotes EMT and Metastasis in Bladder Cancer by the PTEN/AKT Signalling Pathway. (12th April 2022) - Tian, Yong-Hua; He, Yun-Feng; Tan, Jin-Si; Jiang, Yu; Xu, Qiao; Cheng, Hong-Lin
Abstract : Bladder cancer is a common tumour of the urinary system, and more than 90% is urothelial carcinoma. Therefore, it is important for discovering the key target genes and molecules of bladder tumour cell metastasis and invasion. Our research initially explored the regulation of deltaN p63 on the progression and metastasis of bladder cancer and found that deltaN p63 can influence the occurrence of EMT through PTEN and ultimately regulate the growth and metastasis of bladder cancer. In summary, this study identified a new EMT regulator, deltaN p63, further revealed the mechanism of the invasion and metastasis of bladder cancer cells, and provided a theoretical basis for finding new target molecules and drugs to treat bladder cancer. In conclusion, this study will further reveal the mechanism of tumour cell invasion and metastasis and provide a theoretical basis for cancer treatment to find new target molecules and drugs.